“Dear brother farmer”: Gender, agriculture and digital extension in rural Tunisia during the COVID-19 pandemic - Ragetlie, Rosalind; Najjar, Dina; Oueslati, Dorsaf (MDPI, 2023)
Providing farmers with essential agricultural information and training in the era of COVID-19 has been a challenge that has prompted a renewed interest in digital extension services. There is a distinct gender gap, however, between men’s and women’s access to, use of, and ability to benefit from information and communication technologies (ICTs). The overall purpose of this research is to examine how digital extension can address gender inequality in rural areas in the context of the COVID-19 crisis by designing and evaluating the gendered impacts of a digital extension intervention delivered to 624 farmers (363 men and 261 women) (which included phone distribution, radio and SMS messages, and sharing of information prompts) in northern Tunisia. In order to assess the effectiveness of gender-responsive digital extension that targets husband and wife pairs, as opposed to only men, we employed logistic regression and descriptive statistics to analyze a sample of 242 farmers (141 women and 141 men). We find that phone ownership facilitated women’s access to their social network, as well as agricultural information and services, ultimately improving their participation in household decision making and agricultural production. We find that gender-responsive digital extension is effective for men and especially women in terms of usefulness, learning, and adoption. We identified education level and cooperative membership as important factors that determine the impact of digital extension services on farmers and demonstrate the positive impact of radio programming. We recommend strengthening phone access for women, targeting information (including through non-written ways) to both husbands and wives, using sharing prompts, and more rigorous extension for knowledge-intensive topics such as conservation agriculture and rural collectives.